2018
DOI: 10.1186/s13071-018-2807-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antibiotic treatment on the fecundity of Rhipicephalus haemaphysaloides ticks

Abstract: BackgroundEndosymbiotic bacteria inhabit a variety of arthropods including ticks and may have multiple effects on the host’s survival, reproduction or pathogen acquisition and transmission. Rhipicephalus haemaphysaloides is one of the most widely distributed tick species in China. The symbiotic bacteria composition and their impacts to R. haemaphysaloides ticks have not been studied. The present study investigated the composition of microbial community in R. haemaphysaloides ticks and then assessed the effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 25 publications
4
60
1
Order By: Relevance
“…As previously described by Li et al (2018), our results confirm that Coxiella and Rickettsia were the predominant genera in feeding collected ticks. The explanation of this finding could be that these genera were transovarially transmitted, in contrast to other tick endosymbionts that are often obtained from the environment.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…As previously described by Li et al (2018), our results confirm that Coxiella and Rickettsia were the predominant genera in feeding collected ticks. The explanation of this finding could be that these genera were transovarially transmitted, in contrast to other tick endosymbionts that are often obtained from the environment.…”
Section: Discussionsupporting
confidence: 91%
“…We acknowledge that the only way to establish congruent relationships among the detected bacteria, regarding possible events of transmission impairment, is to evaluate the physiological parameters of tick colonies with controlled endosymbiont faunal composition together with dedicated laboratory protocols. However, the presence of R. massiliae in R. sanguineus s.l could act similarly to rickettsial infections in D. variabilis, in which the inhibition of the transovarial transmission of a second Rickettsia has been reported (Ahantarig et al, 2013;De la Fuente et al, 2017;Li et al, 2018;Narasimhan and Fikrig, 2015;Zhong et al, 2007). Although R. massiliae is widespread in R. sanguineus s.l., it has also been recorded in I. ricinus (Bazzocchi et al, 2013;Bonnet et al, 2017;Epis et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine engorged female ticks were randomly assigned to three treatment groups and injected with ciprofloxacin (10 mg/ml), kanamycin (10 mg/ml) or PBS separately, as described previously ( Li et al, 2018 ). In brief, engorged female ticks were injected at the hemocoel between the first and second legs using a Hamilton microinjection syringe (Hamilton Co., Bonaduz, Switzerland).…”
Section: Methodsmentioning
confidence: 99%
“…Rhipicephalus haemaphysaloides , a widely distributed tick species in China ( Chen et al, 2010 ; Yu et al, 2015 ), has been proven to be a vector of B. microti ( Li et al, 2016 ). Our previous study revealed that Rickettsia and Coxiella -like endosymbionts ( Rickettsia -LE and Coxiella -LE hereafter) inhabit R. haemaphysaloides ticks ( Li et al, 2018 ). However, the potential effects of endosymbionts on pathogen susceptibility in this tick species have not been investigated before.…”
Section: Introductionmentioning
confidence: 99%